Eritrea: A Rogue or a Strategically Constructed Threat? - Ylönen, A. (Eritrea: A Rogue or a Strategically Constructed Threat?, 2016)
Eritrea gained independence in 1993 in the post-Cold War context of changing regional political alliances. From the beginning Eritrea‘s relationship with Ethiopia was strained, and following the Eritrean-Ethiopian war (1998-2000) Asmara encountered increasing isolation in the international arena. This paper focuses on aspects of Eritrea’s contemporary political history in the subregional context. It highlights Asmara’s sour relations with some of its powerful neighbors, which have been integrally linked to Eritrea being increasingly portrayed as a regionally destabilizing and terrorism-supporting rogue state. It is therefore argued here that although Eritrea‘s tactics in its foreign afairs have hardly difered from those of other states in the Horn of Africa, the prevailing political realities in the sub-region have resulted in the strategic image of Eritrea as a threat to regional peace and stability.